Mineralogical and textural characterization and its implication in evolution of Santa Isabel de Moro skarn, Ancash - Salas Colca, Ángel Carlos (2022)
Santa Isabel de Moro skarn is a calcic skarn located in the western side of Cordillera Negra in northern Peru, this deposit was originated by intrusion of granodiorite and quartzdiorite in limestones from Santa Formation. The aim of this research is characterized minerals and textures of rocks and mineralization, to determine genesis and evolution of deposit. The methodology used was petrography and X-ray diffraction of samples of outcrops and underground mine, this was integrated of a geological cartography. Detrital rocks were metamorphosed to hornfels, as well as limestone to marble, prograde alteration is composed by garnet, clinopiroxenes and iron oxides, retrograde alteration consists of veinlets of calcite and quartz associated to sulfides. Three styles of mineralization are found in the deposit: I) Fe, II) Cu-Zn, and III) Zn-Pb-Cu-Ag(-Mn); each of them is associated with a different parent pluton, on the other hand, both the host rocks and the mineralization present deformation textures.